PENGARUH KOMPETENSI, PENGUASAAN TEKNOLOGI INFORMASI DAN LINGKUNGAN KELUARGA TERHADAP KESIAPAN KERJA SISWA DENGAN PRAKTIK KERJA INDUSTRI SEBAGAI VARIABEL MODERASI - Nurlita, Anisa; Puji Astuti, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the high unemployment rate of vocational school graduates is still not fully in line with the demands of the world of work. Work readiness is influenced by several internal and external factors such as competence and mastery of information technology as internal factors while family environment and industrial work practices as external factors. The purpose of this study is to analyze the influence of competence, information technology mastery, and family environment, as well as to examine industrial work practice as a moderating variable. This study uses a quantitative approach. The population in this study consists of twelfth-grade students at SMK Negeri 2 Semarang. The sampling technique used is Stratified Proportional Random Sampling, applying the Slovin formula, resulting in a sample of 206 students. Data were collected using questionnaires distributed across five study programs. The data analysis technique used is multiple regression analysis with the assistance of SPSS 26. The results of the study indicate that competence, information technology mastery, and family environment have a positive effect on job readiness. Meanwhile, industrial work practices are able to moderate competence on work readiness but industrial work practices are not able to moderate mastery of information technology and family environment on student work readiness. This study concluded that competency, mastery of information technology, and the family environment are crucial for improving students' work readiness. Schools need to improve the quality of competency learning and strengthen the synergy between the family environment and industry.